Wireless Sensor Networks and Applications - Li, Yingshu; Thai, My T.; Wu, Weili; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
Wireless sensor networks are currently being employed in a variety of applications ranging from medical to military, and from home to industry. Wireless Sensor Networks and Applications aims to provide a reference tool for the increasing number of scientists who depend upon reliable sensor networks. The book is divided into five sections: design and modeling, network management, data management, security, and applications. The eighteen self-contained chapters are authored by experts in wireless networking. Each chapter is given expository but also scholarly treatment, covering the history of its specific topic, reviewing state-of-the-art thinking relative to the topic, and discussing currently unsolved problems of special interest. Key Features: *Explores different access control protocols and wake up strategies in wireless sensor networks; *Discusses several time-synchronization techniques and challenges, i.e., directed diffusion, tiny aggression, greedy aggression on directed diffusion; *Provides insights in network security, i.e., secure routing, and proper management; *Elaborates on numerous wireless sensor network applications, i.e., the ExScal application and the XSM platform. The topics covered within this book are intended for researchers, computer engineers, applied mathematicians, and graduate students interested in wireless sensor networks, but uninformed readers may also find this volume stimulating and helpful.
Network Design and Network Modelling -- A Taxonomy-based Approach to Design of Large-scale Sensor Networks -- Algorithms for Robotic Deployment of WSN in Adaptive Sampling Applications -- A Scalable Graph Model and Coordination Algorithms for Mobile Sensor Networks -- Network Management -- Medium Access Control Protocols for Wireless Sensor Networks -- Topology Control for Wireless Sensor Networks -- Boundary Detection for Sensor Networks -- TPSS: A Time-based Positioning Scheme for Sensor Networks with Short Range Beacons -- Wakeup Strategies in Wireless Sensor Networks -- Time-Synchronization Challenges and Techniques -- Location Service, Information Dissemination and Object Tracking in Wireless Sensor Networks by Using Quorum Methods -- Maximizing the Lifetime of an Always-On Wireless Sensor Network Application: A Case Study -- Data Management -- Data Management in Sensor Networks -- Data Aggregation in Wireless Sensor Networks -- Performance Comparison of Clustering Schemes in Sensor Networks -- Reliable and Efficient Information Forwarding and Traffic Engineering in Wireless Sensor Networks -- Modeling Data Gathering in Wireless Sensor Networks -- Security -- A Survey on Sensor Network Security -- A Passive Approach to Unauthorized Sensor Node Identification.
Keywords: Computer science; Computer communication systems; Computers; Application software; Computer Science; Computer Communication Networks; Models and Principles; Information Systems Applications (incl. Internet).; Computer Appl. in Administrative Data Processing; Electronic books